Differential Adipose Tissue Inflammatory State in Obese Nondiabetic Zucker Fatty Rats Compared to Obese Diabetic Zucker Diabetic Fatty Rats - Miranville, A.; Herling, A. W.; Biemer-Daub, G.; Voss, M. D. (Hormone and Metabolic Research, 2012)
Adipose tissue (AT) inflammation is linked to the pathogenesis of diabetes in obesity. Here, we compare the AT inflammatory state of 2 animal models of obesity and obesity plus diabetes, respectively. Obese nondiabetic ZF rats exhibited a trend towards increased proportions of CD11b positive cells in the adipose tissue stroma vascular fraction suggesting a state of increased AT inflammation compared to their lean littermates, but no alterations in systemic inflammatory parameters. In contrast, obese diabetic ZDF rats exhibited systemic as well as local AT inflammation with elevated levels of circulating Regulated upon Activation, Normal T-cell Expressed and Secreted Protein (Rantes), interleukin 1β (IL-1β) and monocyte chemotactic protein 1 (MCP-1), and an increased infiltration of adipose tissue CD11b positive cells. Our data provide a novel phenotypic characterisation of 2 common metabolic animal models and suggest an association of obesity with local inflammation in adipose tissue, and an association of diabetes with local inflammation in adipose tissue plus systemic inflammation. AT inflammation in obesity might therefore initiate a process that above a certain limits finally results in systemic inflammation and diabetes.
Keywords: adipose tissue; macrophage phenotype; obesity; inflammation